FDG PET/CT of Cardiac Angiosarcoma With Pulmonary Metastases. (October 2018) - Hod, Nir; Shalev, Aryeh; Levin, Daniel; Anconina, Reut; Ezroh Kazap, Dina; Lantsberg, Sophie
Abstract : Abstract: We present a case of an adolescent girl with a cardiac mass which was characterized as malignant on FDG PET/CT. In addition, FDG PET/CT revealed multiple hypermetabolic pulmonary lesions. The final diagnosis was primary cardiac angiosarcoma with pulmonary metastases, a rare malignancy especially in female patients at this age group. We emphasize the potential role of FDG PET/CT in patients with a cardiac neoplasm and present a literature review of FDG uptake in benign versus malignant cardiac tumors.